Versatile strategy for homogeneous drying patterns of dispersed particles - Rey, Marcel; Walter, Johannes; Harrer, Johannes; Perez, Carmen Morcillo; Chiera, Salvatore; Nair, Sharanya Sukumar; Ickler, Maret; Fuchs, Alesa; Michaud, Mark; Uttinger, Maximilian; Schofield, Andrew B.; Thijssen, Job H. J.; et al. (Nature Communications, 2022)
After spilling coffee, a tell-tale stain is left by the drying droplet. This universal phenomenon, known as the coffee ring effect, is observed independent of the dispersed material. However, for many technological processes such as coating techniques and ink-jet printing a uniform particle deposition is required and the coffee ring effect is a major drawback. Here, we present a simple and versatile strategy to achieve homogeneous drying patterns using surface-modified particle dispersions. High-molecular weight surface-active polymers that physisorb onto the particle surfaces provide enhanced steric stabilization and prevent accumulation and pinning at the droplet edge. In addition, in the absence of free polymer in the dispersion, the surface modification strongly enhances the particle adsorption to the air/liquid interface, where they experience a thermal Marangoni backflow towards the apex of the drop, leading to uniform particle deposition after drying. The method is independent of particle shape and applicable to a variety of commercial pigment particles and different dispersion media, demonstrating the practicality of this work for everyday processes.
CRIS-Team WoS Importer:2022-06-10